2023
DOI: 10.3389/fpubh.2023.1194908
|View full text |Cite
|
Sign up to set email alerts
|

eHealth literacy was associated with anxiety and depression during the COVID-19 pandemic in Nigeria: a cross-sectional study

Abstract: BackgroundElectronic health (eHealth) literacy may play an important role in individuals’ engagement with online mental health-related information.AimTo examine associations between eHealth literacy and psychological outcomes among Nigerians during the Coronavirus disease-2019 (COVID-19) pandemic.MethodsThis was a cross-sectional study among Nigerians conducted using the ‘COVID-19’s impAct on feaR and hEalth (CARE) questionnaire. The exposure: eHealth literacy, was assessed using the eHealth literacy scale, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Also, the use of smartphone applications led to a fourfold increase in the practice of BSE among the participants in the intervention group of a study that recommended that women use mobile applications to improve their performance and health beliefs regarding BSE [28]. Similarly, as a high level of mobile phone usage has been reported among this population and Nigerians generally during the COVID-19 pandemic, and Nigerian nurses have successfully designed digital interventions using the internet, mHealth interventions can be designed in Nigeria to teach women BSE techniques [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the use of smartphone applications led to a fourfold increase in the practice of BSE among the participants in the intervention group of a study that recommended that women use mobile applications to improve their performance and health beliefs regarding BSE [28]. Similarly, as a high level of mobile phone usage has been reported among this population and Nigerians generally during the COVID-19 pandemic, and Nigerian nurses have successfully designed digital interventions using the internet, mHealth interventions can be designed in Nigeria to teach women BSE techniques [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we recommend a review of these programmes with research content. Also, as the use of digital devices increased in Nigeria during the COVID‐19 pandemic (Akingbade et al, 2022 ; Akingbade et al, 2023 ), and recent research revealed that Nigerian nurses find virtual learning impactful; continuing education programmes can also leverage online platforms to build research competencies of nurses, as is the case at the Institute of Nursing Research Nigeria (Adesuyi et al, 2023 ). However, it will be important to address the challenges that some might encounter with internet connectivity (Ogbeide et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As nurses effectively deliver various educational interventions among females 34 through various means like mHealth interventions, 35 they can reach females in rural and underserved areas; 36 they should design mHealth interventions focusing on menstrual health for females across Nigeria as a high level of mobile phone usage has been reported among females in Nigeria. 37,38 Similarly, nurses could be involved in early education for females in schools regarding menstrual health.…”
Section: Pacific Rim Int J Nurs Res • October-december 2023mentioning
confidence: 99%